X-ray photochemistry of carbon hydride molecular ions. Issue 6 (26th January 2018) - Puglisi, Alessandra; Miteva, Tsveta; Kennedy, Eugene T.; Mosnier, Jean-Paul; Bizau, Jean-Marc; Cubaynes, Denis; Sisourat, Nicolas; Carniato, Stéphane
Abstract : Ultrafast electronic and nuclear dynamics induced by X-ray absorption in carbon hydride molecular ions are theoretically investigated. Abstract : Hydride molecular ions are key ingredients of the interstellar chemistry since they are precursors of more complex molecules. In regions located near a soft X-ray source these ions may resonantly absorb an X-ray photon which triggers a complex chain of reactions. In this work, we simulate ab initio the X-ray absorption spectrum, Auger decay processes and the subsequent fragmentation dynamics of two hydride molecular ions, namely CH2 + and CH3 + . We show that these ions feature strong X-ray absorption resonances which relax through Auger decay within 7 fs. The doubly-charged ions thus formed mostly dissociate into smaller ionic carbon fragments: in the case of CH2 +, the dominant products are either C + /H + /H or CH + /H + . For CH3 +, the system breaks primary into CH2 + and H +, which provides a new route to form CH2 + near a X-ray source. Furthermore, our simulations provide the branching ratios of the final products formed after the X-ray absorption as well as their kinetic and internal energy distributions. Such data can be used in the chemistry models of the interstellar medium.